CD123-targeted therapy in acute myeloid leukemia. Issue 6 (3rd June 2021) - Espinoza-Gutarra, Manuel Ricardo; Green, Steven D; Zeidner, Joshua F.; Konig, Heiko
ABSTRACT: Introduction: Acute myeloid leukemia (AML) results from the neoplastic transformation of a hematopoietic stem cell. While therapeutic progress has stagnated for several decades, recent progress in the genomic classification of AML has paved the way for multiple new drug approvals. These long-awaited achievements represent a paradigm shift in the approach to a disease that has largely been managed with conventional chemotherapy since the 1970s. With the evolution of targeted AML therapies, novel agents continue to be developed with the goal to improve efficacy while minimizing toxicity. Monoclonal antibodies targeting AML-specific surface markers have emerged as promising candidates to improve outcomes. CD123, interleukin-3 receptor alpha chain [IL-3 Rα], is highly expressed in AML, particularly within the AML stem cell compartment. Several CD123-targeted strategies are currently being evaluated in clinical trials. Areas covered: The authors herein discuss recent clinical data in CD123-directed therapy in AML. A computerized PubMed search was conducted using key words relevant to the various sections of this article. Relevant abstracts presented at the American Society of Hematology, the European Hematology Association, and the American Society of Clinical Oncology were also reviewed. Expert opinion: CD123 represents a suitable therapeutic target that has the potential to improve AML patient outcomes.